Rida by default: Islamic legal perspectives on consent through inaction - Mat Jubri @ Shamsuddin, Mustafa; Md. Sawari, Mohd. Fuad; Mohd Yunus, Saidatolakma (Abrar Global, 2025)
This study explores the Islamic legal perspectives on consent through inaction, focusing on the interplay between riḍā (genuine consent) and default mode decision-making in contemporary contexts. The research problem stems from the increasing prevalence of default settings in commercial, technological, and policy domains, which challenge the classical requirement of explicit consent in Islamic jurisprudence. Employing the method of takyīf fiqhī, the paper analyses default mechanisms through evidences (adillah), legal maxims (qawāʿid fiqhiyyah), and the objectives of Shariah (maqāṣid al-sharīʿah), situating them within the broader framework of contractual validity and enforceability. The analysis reveals that while Islamic law values explicit agreement, default mechanisms can attain conditional legitimacy when they align with principles of maslahah mursalah, customary practice (ʿurf), and Shariah objectives such as facilitation (taysīr) and protection from harm. Key guidelines emerge: defaults must be transparent, serve an overriding public interest (maṣlaḥah rājiḥah), reflect familiar and accepted practices, avoid undue hardship, and preserve the right of all parties to be informed and to override the default through explicit objection. Findings indicate that defects of consent—such as coercion, ignorance, or exploitation—remain decisive in invalidating contracts, even under default arrangements. However, when properly designed, defaults can complement Islamic contractual norms by streamlining processes, reducing decision fatigue, and safeguarding inexperienced parties. The paper concludes that riḍā and default mode are not inherently incompatible; rather, legitimacy hinges on aligning default practices with Shariah principles, ethical safeguards, and the protection of genuine consent. This approach enables Islamic jurisprudence to accommodate contemporary decision-making structures without compromising its foundational values.